New Measures of Gender Inequality: The Social Institutions and Gender Index (SIGI)and its Subindices - Boris Branisa; Stephan Klasen; Maria Ziegler (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
In this paper we construct the Social Institutions and Gender Index (SIGI) and its five subindices Family code, Civil liberties, Physical integrity, Son Preference and Ownership rights using variables of the OECD Gender, Institutions and Development database. Instead of measuring gender inequalities in education, health, economic or political participation, these new indices allow a new perspective on gender issues in developing countries. The SIGI and the subindices measure long-lasting social institutions which are mirrored by societal practices and legal norms that might produce gender inequalities. The subindices measure each one dimension of the concept and the SIGI combines the subindices into a multidimensional index of deprivation of women. Methodologically, the SIGI is inspired by the Foster-Greer-Thorbecke poverty measures. It offers a new way of aggregating gender inequality in several dimensions, penalizing high inequality in each dimension and allowing only for partial compensation between dimensions. The SIGI and the subindices are useful tools to identify countries and dimensions of social institutions that deserve attention. Empirical results confirm that the SIGI provides additional information to that of other well-known gender-related indices.
Keywords: D63; I39; J16; 330; SIGI; Composite index; Gender inequality; Social institutions; OECD-GID database